2017
DOI: 10.1155/2017/9758326
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomena of Naturopathic Practitioner: Predictors of a High Patient Throughput

Abstract: Objective. The aim of the current study was to evaluate which factors predicted a high patient throughput to add more evidence to the phenomena of naturopathic practitioners. Methods. The cross-sectional study was based on a questionnaire with a sample of 1,096 naturopathic practitioners in the German Federal State of Schleswig-Holstein. Besides, sociodemographic data and practice characteristics topics like job satisfaction and feeling for the job were evaluated. This was supplemented with an evaluation of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Ontario’s naturopaths in our study are similar in age to those in prior Canadian [ 18 ], American [ 20 ], and Australian [ 15 , 19 ] studies but about three years younger on average than European naturopaths [ 14 , 16 ]. The province’s TCM/acupuncture practitioners and homeopaths report being similar in age and years of clinical experience to their counterparts in other industrialized countries but, as in other studies, considerably older and with more years of clinical experience than naturopaths.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Ontario’s naturopaths in our study are similar in age to those in prior Canadian [ 18 ], American [ 20 ], and Australian [ 15 , 19 ] studies but about three years younger on average than European naturopaths [ 14 , 16 ]. The province’s TCM/acupuncture practitioners and homeopaths report being similar in age and years of clinical experience to their counterparts in other industrialized countries but, as in other studies, considerably older and with more years of clinical experience than naturopaths.…”
Section: Discussionsupporting
confidence: 77%
“…Ontario's naturopathy, homeopathy and TCM/acupuncture professions are all predominantly comprised of female-identified practitioners, broadly consistent with prior reports of these T&CM occupational groups in other industrialized countries (Table 1). The degree of feminization evident in Ontario's naturopathy profession is, however, slightly lower than that in Germany (16), Switzerland (14) and Australia (17), with an apparent global trend towards increased occupational feminization over the last fifteen years. The moderate occupational feminization of TCM/acupuncture practitioners in our study is similar to that reported in Australian (21) and Swiss ( 14) studies but lower than reported within the American acupuncturist profession [22][23][24]26].…”
Section: Gendermentioning
confidence: 82%
“…In a previous study with complementary medicine practitioners in Germany, a lower average contact time per patient was also associated with a high patient throughput (more than 15 per week) [19]. Although, overall, there was a preponderance of female traditional health practitioners, male practitioners were predominant in high patient throughput, seemingly being more professional, routinely charging consultation fees, spending less consultation time, and operating more often at a special place for practice (analysis not shown) and more often in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Larger surveys among complementary practitioners in Australia, Canada, Germany, New Zealand, Singapore, the UK and the USA found sociodemographic characteristics (most practitioners were female [14,15,16,17], middle-aged, > 40 years old [14,15,17], held a vocational or higher education degree [16,17]) and practice characteristics (most practitioners had 10 or more years of practice [18], most worked full-time [17], part-time [14], had 7-24 clients per week [14,18,19], the initial consultation and treatment lasted for 30-120 min [16], and high referral between complementary and alternative medicine (CAM) and orthodox practitioners [16]). Most complementary practitioners used several treatment modalities [16,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation